2017
DOI: 10.1590/1678-457x.08717
|View full text |Cite
|
Sign up to set email alerts
|

The browning kinetics of the non-enzymatic browning reaction in L-ascorbic acid/basic amino acid systems

Abstract: Under the conditions of weak basis and the reaction temperature range of 110-150 °C, lysine, arginine and histidine were reacted with L-ascorbic acid at equal amount for 30-150 min, respectively and the formation of browning products was monitored with UV-vis spectrometry. The kinetic characteristics of their non-enzymatic browning reaction were investigated. The study results indicated that the non-enzymatic browning reaction of these three amino acids with L-ascorbic acid to form browning products was zero-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 26 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…The measurement of the absorbance at 420 nm in a T70 + UV–Visible Spectrophotometer (PG instruments Ltd, UK) is a way to monitor the reaction process of the non‐enzymatic browning reactions, the Maillard reaction and the caramelization, i.e ., to know the status of the formation of the browning products . This is of prime importance as both reactions affect the quality of processed products in relation to the sensory attributes (color, flavour and taste) …”
Section: Methodsmentioning
confidence: 99%
“…The measurement of the absorbance at 420 nm in a T70 + UV–Visible Spectrophotometer (PG instruments Ltd, UK) is a way to monitor the reaction process of the non‐enzymatic browning reactions, the Maillard reaction and the caramelization, i.e ., to know the status of the formation of the browning products . This is of prime importance as both reactions affect the quality of processed products in relation to the sensory attributes (color, flavour and taste) …”
Section: Methodsmentioning
confidence: 99%
“…Of the non-enzymatic browning processes, it is Maillard reaction, involving reducing sugars with amino acids, protein and protein derivatives, that has received much attention from workers like Quayson and Ayernor (2007), Hemmler et al (2018) and Yu et al (2018). Although the reaction results in loss of essential amino acids, various studies in model systems and natural foods have reported the presence of products that have antioxidants activities (Phisut and Jiraporn, 2013;Wijewickreme and Kitts, 1997;Bedinghaus and Ockerman, 1995;Wijewickreme and Kitts, 1998a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Of the non-enzymatic browning processes, it is Maillard reaction, involving reducing sugars with amino acids, protein and protein derivatives, that has received much attention from workers like Quayson and Ayernor (2007) , Hemmler et al. (2018) and Yu et al. (2018) .…”
Section: Introductionmentioning
confidence: 99%
“…However, films with low fiber content showed good transparency, satisfying a fundamental characteristic for some packaging applications. The yellowing/browning of the TPWF films, which it is normally caused by the non-enzymatic reactions that occur during plasticization, is emphasized by the presence of the bran, which adds opacity and darkening [ 16 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%